2015
DOI: 10.1016/j.jinf.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Differences in serum microRNA profiles in hepatitis B and C virus infection

Abstract: Serum microRNA levels reflect differences in the etiology and stage of viral hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 56 publications
(49 reference statements)
8
43
1
Order By: Relevance
“…Even modest amount of alcohol consumption has been show to elevate serum miR-122 levels51. Pathological states in the liver [NAFDL1828, ALD23 cirrhosis52, cancer29, toxicity53 and infection31] have all been shown to be associated with altered serum/plasma levels of miR-122. In support to our results associating hsa-miR-122-5p levels with liver enzyme levels, the serum levels of miR-122 have been previously shown to be associated with ALT and total cholesterol in hepatitis C patients receiving a nucleic acid-based miR-122 inhibitor54.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even modest amount of alcohol consumption has been show to elevate serum miR-122 levels51. Pathological states in the liver [NAFDL1828, ALD23 cirrhosis52, cancer29, toxicity53 and infection31] have all been shown to be associated with altered serum/plasma levels of miR-122. In support to our results associating hsa-miR-122-5p levels with liver enzyme levels, the serum levels of miR-122 have been previously shown to be associated with ALT and total cholesterol in hepatitis C patients receiving a nucleic acid-based miR-122 inhibitor54.…”
Section: Discussionmentioning
confidence: 99%
“…Even a serum miRNA expression panel consisting of hsa-miR-122-5p, -1290, -27b-3p, and -192-5p has been suggested for clinical NAFLD diagnostics18. Studies have shown increased levels of circulatory miR-122 in liver diseases with different etiologies18202328293031, indicating that it may be a potential marker for liver injury. In addition, for example the circulatory miRNAs related to inflammation, such as miR-21, -34a, -45128 and -155 have been associated to NAFLD (reviewed in refs 32 and 33).…”
mentioning
confidence: 99%
“…In addition, they have a role in normal liver development and liver diseases . It was noticed that some viruses may disrupt complex miRNA regulatory networks, resulting in changes in their expression inside and outside of the cell …”
Section: Introductionmentioning
confidence: 99%
“…In a study, it was revealed that increasing level of GGT was significantly related with changes of expression level of miR-22 and miR-1275 (55). In other researches, the abnormal expression levels of these two microRNAs were testified to promote anti-apoptosis and tumor growth (56)(57)(58).…”
Section: Ggt As a Functional Macromolecule In Mechanistic Studiesmentioning
confidence: 99%